Prison officers' experiences of working with adult male offenders who engage in suicide-related behaviour. Issue 3 (4th May 2018) - Sweeney, Fiona; Clarbour, Jane; Oliver, Antony
Abstract: Suicide-related behaviour amongst adult male offenders within the Prison Service is currently at record levels. However, the impact of this behaviour on prison officers has been largely overlooked. Therefore, the purpose of this paper aims to develop an understanding of prison officers' experiences of working with suicide-related behaviour. As limited research has been conducted in this area, semi-structured interviews were conducted to explore participants' thoughts, feelings, coping strategies and avenues of support. Nine prison officers were interviewed and thematic analysis was applied to transcripts. Thematic analysis identified five themes: prison officer culture limiting support, feeling unqualified, under-resourced, minimising negative emotions and positivity. The results highlight the specific challenges faced by officers when working with suicidal behaviour, alongside more general challenges facing public services in the current times. Recommendations are made about how organisations could mediate these challenges and better support staff.